DEVELOPING AN INTERACTIVE PROJECT-BASED LEARNING E-LKPD TO FACILITATE CREATIVE MATHEMATICAL THINKING SKILLS - Andi Saputra Mandopa; Adek Nilasari Harahap; Puspa Riani Nasution (Aksioma: Jurnal Program Studi Pendidikan Matematika, 2024)
The urgency of this research is due to the limited learning resources that support the development of creative thinking in mathematics, which is an essential skill in the 21st century. This research aims to develop an interactive E-LKPD based on Project Based Learning (PjBL) that is valid, practical and effective in facilitating creative mathematical thinking skills in junior high school students.. The method used is research and development (R&D) by applying the 4-D model which includes the stages of defining, designing (design), development, and dissemination. The resulting product was tested for validity by a team of material and design experts with an average score of 3.28, and its practicality and effectiveness were assessed through student and teacher responses with an average total practical score of 3.5. Evaluation of improving mathematical creative thinking abilities using PjBL-based E-LKPD shows an average score of 80.86, which is included in the very high category with a completeness level reaching 89.65%. Thus, the PjBL-based E-LKPD is suitable for use because it meets the criteria of being valid, practical and effective. The implication of this research is the need for further development of the model used to produce products that are higher quality and more effective in supporting the creative mathematical learning process.